Case Report: Myocardial dissection caused by ruptured sinus of Valsalva aneurysm in association with a bicuspid aortic valve - Zhou, Xinyan; Xu, Yan; He, Qian; Tan, Na; Chu, Jixiang; Liu, Bin; Zhu, Yu; Liao, Chengde; Jiang, Yu (Frontiers in Cardiovascular Medicine, 2023)
In this report, we present a case of left-right sinus fusion in a Ruptured sinus of Valsalva aneurysm (RSVA) that perforated into the myocardium, giving rise to myocardial dissection. The existence of an anomalous bicuspid aortic valve (BAV) is contemplated as a potential etiological element in this context. Employing multimodal imaging modalities, encompassing transthoracic echocardiography and computed tomography (CT), facilitated the visualization of a dissecting hematoma situated within the myocardium subsequent to the RSVA. Following this, our patient underwent an Cabrol surgical intervention, received patch repair, and underwent mitral valve annuloplasty, during which a three-year period transpired without the occurrence of any deleterious cardiac events. In summary, this report establishes the cornerstone for the surgical intervention of RSVA, shedding light on the efficacious handling of RSVA-associated myocardial dissection. It posits that the presence of a BAV may serve as a predisposing factor to RSVA rupture, potentially elevating the susceptibility to myocardial dissection. The utilization of diverse multimodal imaging methodologies played an indispensable role in the detection of a hematoma within the myocardial tissue subsequent to the RSVA rupture. The uneventful three-year postoperative follow-up of the patient underscores the efficacy of the undertaken interventions.